Nano-crystal magnetic core with full-band high magnetic conductivity as well as preparation method and application of nano-crystal magnetic core
Through force-magnetic composite heat treatment technology, the precipitation and growth of nanocrystalline magnetic cores are regulated, and the problem of limited magnetic permeability improvement in nanocrystalline magnetic core materials in the high frequency band are realized. In new energy vehicles and other high-performance equipment.
Patent Information
- Application Number
- CN202411588562.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-18
AI Technical Summary
In the prior art, the magnetic permeability improvement of nanocrystalline magnetic cores in the high frequency band is limited, and the limitations of heat treatment and magnetic field action lead to poor permeability in the entire frequency band.
Force-magnetic composite heat treatment technology is adopted to induce nanocrystallisation of amorphous alloys through two heat treatments and magnetic field heat treatment, and regulate the precipitation, size and growth orientation of nanocrystallises to improve magnetic permeability.
The magnetic permeability of nanocrystalline magnetic cores in the entire frequency band of 1-100kHz has been achieved, especially at the high frequency of 100kHz, the magnetic permeability can reach more than 45,000, meeting the high performance of new energy vehicles, photovoltaic energy storage and other fields. need.
Smart Images

Figure CN119480409A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of magnetic materials, and in particular relates to a nanocrystalline magnetic core with high magnetic permeability over a full frequency range, and a preparation method and application thereof. Background Art
[0002] Benefiting from the accelerated application of the third-generation wide bandgap semiconductor power devices, the development of high-frequency and high-efficiency inductors and high-power density transformers matching them towards miniaturization, integration and low energy consumption has become an inevitable trend. As a new generation of "double green" energy-saving materials, iron-based amorphous / nanocrystalline soft magnetic alloys are considered to be ideal materials for the preparation of high-frequency and high-efficiency inductors and high-power density transformers because of their excellent comprehensive soft magnetic properties, such as high saturation magnetic induction intensity, low coercive force, high magnetic permeability, and low loss.
[0003] Iron-based amorphous / nanocrystalline soft magnetic alloys are usually made of amorphous strips through a high-speed copper roller rapid cooling process from the master alloy, and the amorphous strips are wound into amorphous cores. Amorphous cores generally need to undergo appropriate heat treatment processes to finely control the microstructure of the alloy, that is, a single magnetic α-Fe phase is precipitated on the amorphous matrix and transformed into a dual-phase coexistence structure of amorphous and nanocrystalline to form a nanocrystalline core. This special dual-phase nanostructure is also the main reason why the nanocrystalline core exhibits excellent comprehensive soft magnetic properties. Therefore, the heat treatment process of the core plays a decisive role in obtaining high-performance nanocrystalline cores. Annealing is carried out in conventional heat treatment methods for amorphous cores, such as in an atmosphere furnace.
[0004] Limited by the slow heating / cooling rate in the industrial furnace, the amorphous core will not be completely precipitated when subjected to high-temperature heat treatment. On the one hand, if the heating time is too short, the grains will not be completely precipitated. On the other hand, if the heating time is too long, the grains will be unevenly precipitated and grow excessively. Both of these situations will deteriorate the performance of the obtained nanocrystalline core, especially significantly reduce the magnetic permeability of the nanocrystalline core. In essence, the main reason why the nanocrystalline core exhibits excellent soft magnetic permeability is: first, optimizing the heat treatment process, controlling the precipitation and growth of nanocrystalline grains by adjusting the appropriate heat treatment temperature and holding time, and obtaining fine and uniform nanocrystalline grains on the amorphous matrix to form an amorphous and nanocrystalline dual-phase composite structure; second, using the magnetic field to induce grain orientation growth, causing the nanocrystalline grains to orient along the direction of the magnetic field, thereby inducing magnetic anisotropy and regulating the shape of the hysteresis loop. However, on the one hand, since the crystallization process of amorphous alloys is sensitive to heat treatment temperature and time, the precipitation and growth of nano-grains in existing heat treatment technology can only depend on the length of temperature action time, resulting in the size and distribution of nano-grains being difficult to be effectively controlled, and the improvement of magnetic permeability is limited; on the other hand, due to the limitation of magnetic field intensity, magnetic field annealing is difficult to make all nano-grains turn, and at the same time, due to the singleness of the direction of magnetic field application to the magnetic core, the magnetic permeability performance can only be optimized for a specific frequency band of the nanocrystalline magnetic core, that is, the low-frequency magnetic permeability (below 50kHz) can be improved, and the high-frequency magnetic permeability (above 50kHz) can be reduced, or the high-frequency magnetic permeability (above 50kHz) can be improved, and the low-frequency magnetic permeability (below 50kHz) can be reduced. Therefore, whether it is conventional heat treatment or magnetic field action, the improvement of the magnetic permeability of nanocrystalline magnetic cores is very limited, especially at high frequencies, the increase in magnetic permeability is limited, and a new amorphous magnetic core preparation technology is urgently needed to improve the magnetic permeability of nanocrystalline magnetic cores. Summary of the invention
[0005] In view of the problem of low magnetic permeability of nanocrystalline magnetic cores in the above-mentioned prior art, the present invention will provide a nanocrystalline magnetic core with high magnetic permeability over the entire frequency band, and a preparation method and application thereof.
[0006] To achieve the above purpose, the following technical solutions are specifically included:
[0007] A method for preparing a nanocrystalline magnetic core comprises the following steps:
[0008] (1) subjecting the amorphous magnetic core to a first heat treatment and a second heat treatment in sequence, cooling and reducing the pressure to obtain a pre-burned magnetic core; the temperature of the first heat treatment is 490-520° C., and the temperature of the second heat treatment is 550-600° C.; the pressure of the first heat treatment and the second heat treatment is greater than atmospheric pressure;
[0009] (2) The pre-burned magnetic core is subjected to magnetic field heat treatment and, after cooling, the nanocrystalline magnetic core is obtained.
[0010] In the method of the present invention, nanocrystallization of amorphous alloys is induced by force-magnetic composite heat treatment technology, which effectively solves the problems of uneven nucleation and excessive growth of nanocrystals in conventional heat treatment, comprehensively improves the comprehensive electromagnetic properties of nanocrystalline magnetic cores, and obtains nanocrystalline magnetic core materials with high magnetic permeability in the full frequency band, especially the magnetic permeability in the high frequency band, which can be as high as 45,000 or more, effectively solving the defect of low magnetic core in the high frequency band.
[0011] In the method of the present invention, in step (1), the first heat treatment and the second heat treatment are mainly aimed at crystallizing the amorphous magnetic core, aiming to promote the precipitation of a large number of fine α-Fe nano-grains on the amorphous matrix; in step (2), the grains in the magnetic core are induced to grow in an oriented manner along the direction of the magnetic field through the action of the magnetic field while precipitating and growing, and appropriate magnetic anisotropy is introduced under the action of the external magnetic field; therefore, the precipitation, size and growth orientation of nano-grains are regulated by the method of the present invention, thereby improving the comprehensive soft magnetic properties of the obtained nanocrystalline magnetic core.
[0012] Preferably, in step (1), the pressure of the first heat treatment is 20-60 MPa, the time of the first heat treatment is 20-120 min, and the heating rate of the first heat treatment is 1-30° C. / min.
[0013] Preferably, the pressure of the second heat treatment is 30-120 MPa, the time of the second heat treatment is 30-90 min, the heating rate of the second heat treatment is 1-5° C. / min, and the cooling rate is 5-600° C. / min.
[0014] Preferably, in step (1), the pressurization methods of the first heat treatment and the second heat treatment are each selected from at least one of pressurization by inert gas pressure and pressurization by mold extrusion; the amorphous magnetic core in step (1) is formed by winding an amorphous strip, and the magnetic field direction of the magnetic field heat treatment in step (2) is parallel to the width direction of the amorphous magnetic core.
[0015] Preferably, in step (1), the amorphous magnetic core comprises the following elements in atomic percentage: Fe 60-80%, Si 10-20%, B 0-10%, Cu 0-3%, Nb 0-5%, Ni 0-15%, Co 0-10%, V 0-10%.
[0016] Further preferably, the amorphous magnetic core is Fe 73.5 Si 15.5 B7Cu1Nb3、Fe 73.5 Si 15.5 B7Cu1V1Nb2、Fe 73.5 Si 13.5 B9Cu1Nb3、Fe63.5 Ni 10 Si 15.5 B7Cu1Nb3、Fe 63.5 Co5Ni5Si 15.5 B7Cu1Nb3、Fe 68.5 Co5Si 15.5 At least one of B7Cu1Nb3.
[0017] Preferably, in step (1), the cooling and depressurization are performed by first naturally cooling the system to below 200° C. and then releasing the pressure of the system to atmospheric pressure.
[0018] Preferably, in step (2), the temperature of the magnetic field heat treatment is 460-530° C., the time of the magnetic field heat treatment is 1-180 min, and the magnetic field intensity of the magnetic field heat treatment is 800-3000 Gs.
[0019] Preferably, in step (2), the rate of heating to the magnetic field heat treatment temperature is 1-20°C / min.
[0020] Preferably, in step (2), the cooling method is natural cooling.
[0021] Preferably, the magnetic permeability of the nanocrystalline magnetic core is greater than or equal to 45,000.
[0022] Further preferably, at a frequency of 1 kHz, the magnetic permeability of the nanocrystalline magnetic core is 80,000-120,000, at a frequency of 10 kHz, the magnetic permeability of the nanocrystalline magnetic core is 70,000-110,000, and at a frequency of 100 kHz, the magnetic permeability of the nanocrystalline magnetic core is 45,000-60,000.
[0023] The present invention also provides an application of the nanocrystalline magnetic core in the preparation of new energy vehicles, photovoltaic energy storage equipment, electronic camera equipment, and 5G communication equipment. The nanocrystalline magnetic core of the present invention has a high magnetic permeability and is more suitable for use in the preparation of the above-mentioned equipment.
[0024] Compared with the prior art, the present invention has the following beneficial effects: the present invention induces nanocrystallization of amorphous alloys through force-magnetic composite heat treatment technology, effectively solving the problems of uneven nucleation and excessive growth of nanocrystals in conventional heat treatment, so that the magnetic permeability of the magnetic core in the entire frequency range of 1-100kHz is significantly improved, especially at a high frequency of 100kHz, it has an effective magnetic permeability of more than 45,000, which meets the application requirements of industrial fields such as new energy vehicles, photovoltaic energy storage, consumer electronics, 5G communications, etc. for high-performance nanocrystalline magnetic cores. At the same time, the heat treatment method is universal for nanocrystalline magnetic powder cores and strips. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1This is the X-ray diffraction (XRD) pattern of the homemade amorphous ribbon.
[0026] Figure 2 It is a microstructure comparison diagram between Example 1 (left) and Comparative Example 3 (right).
[0027] Figure 3 This is a physical picture of the magnetic core prepared in Example 1.
[0028] Figure 4 Graph showing the relationship between the effective magnetic permeability and frequency of the iron-based nanocrystalline soft magnetic alloy cores of Examples 1 to 12.
[0029] Figure 5 This is a graph showing the relationship between the effective magnetic permeability and frequency of the iron-based nanocrystalline soft magnetic alloy cores of comparative examples 1 to 4. DETAILED DESCRIPTION
[0030] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below through specific examples. The test methods used in the examples and / or comparative examples are conventional methods unless otherwise specified; the materials, reagents, etc. used can be obtained from commercial channels unless otherwise specified.
[0031] Amorphous strips can be made by yourself or purchased from the market. The Fe 73.5 Si 15.5 B7Cu1Nb3 is a self-made amorphous ribbon made by conventional process. Its XRD is shown in the attached Figure 1 The homemade method may include the following processes: (1) component ratio; (2) master alloy smelting; (3) then spinning and coiling the strip to obtain the corresponding amorphous strip.
[0032] Example 1
[0033] (1) The alloy Fe in atomic percentage 73.5 Si 15.5 The B7Cu1Nb3 amorphous strip is wound into an amorphous magnetic core, and then the amorphous magnetic core is placed in a gas furnace body, evacuated, filled with inert gas argon gas so that the system has a certain gas pressure, heated to the first heat treatment temperature of 500°C at a heating rate of 10°C / min, and at the same time, argon gas is continuously filled to pressurize to the first heat treatment pressure of 30MPa, and the temperature and pressure are maintained for 90 minutes;
[0034] (2) Continue heating and pressurizing, continue heating to the second heat treatment temperature of 580°C at a heating rate of 3°C / min, and continue to fill with argon gas to pressurize to the second heat treatment pressure of 60MPa, and keep the temperature and pressure at this temperature and pressure for 60min; then cool down to below 200°C, start to release the pressure to room pressure, and set the cooling rate to natural cooling with the furnace to obtain a pre-burned magnetic core;
[0035] (2) Magnetic field heat treatment: The pre-burned magnetic core is placed in the magnetic field heat treatment furnace and heated to 500°C at a heating rate of 10°C / min. At this time, a magnetic field parallel to the width direction of the amorphous strip is added, and the magnetic field strength is 1500Gs. The magnetic field heat treatment is carried out at this temperature and magnetic field for 60 minutes, and the temperature is cooled to room temperature with the furnace to obtain a nanocrystalline magnetic core.
[0036] Examples 2-12 and Comparative Examples 1-4
[0037] The only difference between Examples 2-12 and Comparative Examples 1-4 and Example 1 is: in steps (1)-(3), the heating rate or temperature or pressure of the first heat treatment, the heating rate or temperature or pressure of the second heat treatment, the magnetic field heat treatment temperature or magnetic field intensity and time. The detailed differences are shown in Table 1.
[0038] Table 1
[0039]
[0040] The performance of the nanocrystalline magnetic core prepared above was tested: the inductance L of the magnetic core was tested using a Keysight Agilent 4294A precision impedance analyzer in an external magnetic field of 1A / m and a frequency range of 1kHz to 100kHz; the effective magnetic permeability μ e Obtained through the inductance L conversion formula:
[0041] μ e =(L×L e ) / (N 2 ×A e ),
[0042] Where, L is the core inductance, μ e is the effective magnetic permeability of the core, L e is the magnetic path length of the core, A e is the effective cross-sectional area of the core, N is the number of coil turns (the test condition is 1 turn), and the test results are shown in Table 2.
[0043] Conventional heat treatment process is the preparation method in Comparative Example 3. Now, the magnetic core prepared in Comparative Example 3 is used as a basis for comparison to calculate the change rate X of the magnetic permeability of the magnetic core of other embodiments of the present invention and the conventional heat treatment process Comparative Example 3: X f =(μ n -μ 对比例3 ) / μ 对比例3 *100%, where μ n Refers to the effective magnetic permeability of a magnetic core obtained in a certain embodiment or comparative example at frequency f, μ 对比例3 Refers to the effective magnetic permeability of the magnetic core prepared in Comparative Example 3 at frequency f, and the results are shown in Table 2.
[0044] Table 2
[0045]
[0046] It can be seen from the TEM image and grain distribution diagram in Comparative Example 3 that the sample will have the problem of uneven heating in conventional heat treatment, resulting in uneven nucleation of nano-grains, incomplete precipitation of grains and excessive growth. Therefore, the present invention first performs a first heat treatment to make the amorphous magnetic core evenly heated, providing a basis for the second heat treatment; then the temperature is increased and / or the pressure is continued to be increased, through a slow heating rate and selecting a suitable holding time, to ensure that the grains have enough time to precipitate at a higher temperature, and grow slowly and evenly under the action of air pressure, avoiding uneven heating caused by overheating, or avoiding incomplete precipitation of grains due to too short a time, or excessive growth of grains due to too long a holding time; finally, combined with magnetic field heat treatment, the nano-grains are completely turned, and the force field heat treatment and magnetic field heat treatment as a whole make the grains in the nanocrystalline magnetic core completely precipitated and uniform in size, as shown in the attached figure. Figure 2 As shown, the purpose of improving the magnetic permeability of the nanocrystalline core in the full frequency band is achieved.
[0047] In the above-mentioned embodiments 1-12, at a frequency of 1kHz, the effective magnetic permeability of the nanocrystalline magnetic core is 80,000-120,000; at 10kHz, the effective magnetic permeability of the nanocrystalline magnetic core is 70,000-110,000; at 100kHz, the effective magnetic permeability of the nanocrystalline magnetic core is 45,000-60,000. Compared with comparative examples 1-4, at 1-100kHz, the degree of improvement of the magnetic permeability of embodiments 1-12 is significantly higher, especially at a high frequency of 100kHz, the effective magnetic permeability is as high as 45,000 or more.
[0048] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a nanocrystalline magnetic core, characterized in that: The steps include: (1) subjecting the amorphous magnetic core to a first heat treatment and a second heat treatment in sequence, cooling and reducing the pressure to obtain a pre-burned magnetic core; the temperature of the first heat treatment is 490-520° C., and the temperature of the second heat treatment is 550-600° C.; the pressure of the first heat treatment and the second heat treatment is greater than atmospheric pressure; (2) The pre-burned magnetic core is subjected to magnetic field heat treatment and cooled to obtain the nanocrystalline magnetic core.
2. The method for preparing a nanocrystalline magnetic core according to claim 1, characterized in that: In step (1), the pressure of the first heat treatment is 20-60 MPa, the time of the first heat treatment is 20-120 min, and the heating rate of the first heat treatment is 1-30° C. / min.
3. The method for preparing a nanocrystalline magnetic core according to claim 1, characterized in that: In step (1), the pressure of the second heat treatment is 30-120 MPa, the time of the second heat treatment is 30-90 min, the heating rate of the second heat treatment is 1-5°C / min, and the cooling rate is 5-600°C / min.
4. The method for preparing a nanocrystalline magnetic core according to claim 1, characterized in that: In step (1), the pressurization methods of the first heat treatment and the second heat treatment are each selected from at least one of pressurization by inert gas pressure and pressurization by mold extrusion; the amorphous magnetic core in step (1) is formed by winding an amorphous strip, and the magnetic field direction of the magnetic field heat treatment in step (2) is parallel to the width direction of the amorphous magnetic core.
5. The method for preparing a nanocrystalline magnetic core according to claim 1, characterized in that: In step (1), the amorphous magnetic core comprises the following elements in atomic percentage: Fe 60-80%, Si 10-20%, B 0-10%, Cu 0-3%, Nb 0-5%, Ni0-15%, Co 0-10%, V 0-10%.
6. The method for preparing a nanocrystalline magnetic core according to claim 1, characterized in that: In step (2), the temperature of the magnetic field heat treatment is 460-530° C., the time of the magnetic field heat treatment is 10-90 min, and the magnetic field intensity of the magnetic field heat treatment is 800-3000 Gs.
7. The method for preparing a nanocrystalline magnetic core according to claim 1, characterized in that: In step (1), the cooling and depressurization method is to first naturally cool the system to below 200° C. and then release the pressure of the system to atmospheric pressure; in step (2), the cooling method is natural cooling.
8. A nanocrystalline magnetic core made by the method for making a nanocrystalline magnetic core according to any one of claims 1 to 7.
9. The nanocrystalline magnetic core according to claim 8, characterized in that: At a frequency of 1kHz, the magnetic permeability of the nanocrystalline magnetic core is 80,000-120,000, at a frequency of 10kHz, the magnetic permeability of the nanocrystalline magnetic core is 70,000-110,000, and at a frequency of 100kHz, the magnetic permeability of the nanocrystalline magnetic core is 45,000-60,000.
10. Use of the nanocrystalline magnetic core according to claim 8 or 9 in the preparation of new energy vehicles, photovoltaic energy storage equipment, electronic camera equipment, and 5G communication equipment.
Citation Information
Patent Citations
Preparation method of amorphous nanocrystalline alloy with high magnetic permeability
CN111057970A
Ultrahigh-permeability iron-based nanocrystalline soft magnetic alloy magnetic core and heat treatment method thereof
CN112908673A
Preparation method of high-permeability iron-based nanocrystalline soft magnetic alloy magnetic core
CN112927914A
Heat treatment method of broadband ultrahigh frequency iron-based nanocrystalline alloy special-shaped magnetic core
CN115747453A
Iron-based amorphous magnetic core material, nanocrystalline magnetic core, magnetic conductive sheet and preparation method of iron-based amorphous magnetic core material
CN116130195A